Orchids Cytogenetics and Karyotype of Phaius callosus and Phaius montanus - Sri Hartati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
The Phaius callosus and Phaius montanus orchids are ornamental orchids with high ornamental value and are classified as endangered plants. Genetic information from Phaius callosus and Phaius montanus orchids will facilitate plant breeding as it is essential to improve ornamental plant properties. Chromosome analysis aims to determine chromosomes' shape, number, and size. The research was conducted at the Cytology Laboratory of the LIPI Biology Research Center, Bogor, West Java. Analysis of research results based on observations of shooting results and data on the size and shape of chromosomes was carried out descriptively. The chromosome number of Phaius callosus and Phaius montanus had a similarity of 2n = 46, metacentric in shape. The chromosome size of Phaius callosus was 1.30 ± 0.29, while that of Phaius montanus was 2.32 ± 1.01. The karyotype formula of Phaius callosus and Phaius montanus had a similarity of 2n=46=23m which was dominantly metacentric.